The Adequacy of Anesthesia Guidance for Vitreoretinal Surgeries with Preemptive Paracetamol/Metamizole - Michał Jan Stasiowski; Anita Lyssek-Boroń; Nikola Zmarzły; Kaja Marczak; Beniamin Oskar Grabarek (MDPI AG, 2024)
Despite the possibility of postoperative pain occurrence, in some patients, vitreoretinal surgeries (VRSs) require performance of general anesthesia (GA). The administration of intraoperative intravenous rescue opioid analgesics (IROA) during GA constitutes a risk of perioperative adverse events. The Adequacy of Anesthesia (AoA) concept consists of an entropy electroencephalogram to guide the depth of GA and surgical pleth index (SPI) to optimize the titration of IROA. Preemptive analgesia (PA) using cyclooxygenase-3 (COX-3) inhibitors is added to GA to minimize the demand for IROA and reduce postoperative pain. The current analysis evaluated the advantage of PA using COX-3 inhibitors added to GA with AoA-guided administration of IROA on the rate of postoperative pain and hemodynamic stability in patients undergoing VRS. A total of 165 patients undergoing VRS were randomly allocated to receive either GA with AoA-guided IROA administration with intravenous paracetamol/metamizole or with preemptive paracetamol or metamizole. Preemptive paracetamol resulted in a reduction in the IROA requirement; both preemptive metamizole/paracetamol resulted in a reduced rate of postoperative pain as compared to metamizole alone. We recommend using intraoperative AOA-guided IROA administration during VRS to ensure hemodynamic stability alongside PA using both paracetamol/metamizole to reduce postoperative pain.